Konstruktivisme Sebagai Faktor Pengaruh Terbentuknya Hubungan Paradiplomasi Kerjasama Sister City Antar Kota Surabaya Dengan Gaziantep - Michael Samudra Djaja; Muhammad Indrawan Jatmika (STISIPOL Raja Haji, 2026)
The increasing practice of paradiplomacy through sister city cooperation has not been fully balanced with studies that explain the ideological motives behind the selection of city partners, so the majority of research still focuses on administrative aspects or material interests. This study is present to analyze the formation of the SurabayaGaziantep sister city cooperation for the 2019–2021 period through the perspective of constructivism using a descriptive qualitative method based on document studies. The results of the study show that the formation of cooperation between the two cities is directly influenced by the ideological similarities that they have, including identities, norms, and cultures that are perceived together as the basis for the feasibility of choosing city partners. This similarity is reflected in the image of the two cities as industrial cities and historical cities, the leadership of the community that represents gender equality norms, and the similarity of architectural and culinary cultural heritage. Thus, the cooperation between the City of Surabaya and Gaziantep has proven to be more effective in implementing aspects of joint ideas in the practice of paradiplomacy which is not just the result of calculation of practical interests. Although the COVID-19 pandemic partially postponed the cooperation agenda, the commitment of the two cities was maintained until it was formalized through the signing of an MoU in 2021.